Understanding and shaping the athlete's brain using body-mind reading and feedback - Kashino, M (MMSports'18 Proceedings of the 1st International Workshop on Multimedia Content Analysis in Sports - Seoul, Republic of Korea — October 26 - 26, 2018, 2018)
In sports where athletes play against an opponent, for example, ballgames and martial arts, a variety of cognitive functions hold the key to winning, such as grasping the situation, strategizing against one's opponent, making appropriate decisions instantaneously, and keeping an ideal mental state under intense pressure. Most of these functions, however, are "implicit" brain functions that the athlete himself/herself is not even aware of and cannot control at will. This is thought to be one of the factors behind the difficulty of acquiring, exhibiting, and coaching a specific skill. The NTT Sports Brain Science project was established in January 2017 to conduct research with the aim of understanding superior implicit brain functions in top athletes, identifying the factors in winning, and improving the performance of athletes based on research findings. The technical core of the project is "body-mind reading and feedback", which is constituted by various technologies such as wearable sensing, computer vision, biometric analyses, virtual reality, and sonification. The basic concepts and some research topics of the project will be introduced, with a focus on baseball and softball.